Facile Aldolization Catalyzed by Ionic Liquid [4-Sulfbmpyrazine][BF4] - Zou, Jianzhong; Yi, Fengping; Zhang, Lirong; Wang, Zhen (Asian Journal of Chemistry, 2013)
The acidic functionalized ionic liquid 1-(4-sulfonic group)butyl-3-methylpyrazine tetrafluoroborate (abbreviated as [4-sulfbmpyrazine][BF4]) was employed as the catalyst of the condensation of aromatic aldehyde and diols. The optimized condition was as follows: aromatic aldehyde (0.20 mol), diols (0.30 mol) and [4-sulfbmpyrazine][BF4] (0.60 g) were refluxed in cyclohexane (10.00 mL) for 1 h. A series of aromatic aldehydes were studied and afforded the corresponding acetals products with good yields which were from 70.3 to 96.9 %. The ionic liquid catalyst could be recycled for four times without significant loss of catalyst reactivity.